Encyrtidae (Hymenoptera: Chalcidoidea) from the Kingdom of Saudi Arabia - Hayat, Mohammad; Ahmad, Zubair; Khan, Farmanur Rehman (Zootaxa, 2014)
This is the first major contribution to the fauna of the family Encyrtidae (Hymenoptera: Chalcidoidea) of the Kingdom of Saudi Arabia. The following new genus and 15 new species are described: Anagyrus azolus Hayat, sp. nov., A. raidahensis Hayat, sp. nov., Arabencyrtus qahtanii Hayat, gen. et sp. nov., Cerchysiella arabia Hayat, sp. nov., C. azeeza Hayat, sp. nov., Cheiloneurus arabiacus Hayat, sp. nov., Leptomastidea abyad Hayat, sp. nov., Mahencyrtus asirensis Hayat, sp. nov., Metaphycus albidus Hayat, sp. nov., Microterys axonis Hayat, sp. nov., Neastymachus bolus Hayat, sp. nov., N. ceelus Hayat, sp. nov., Ooencyrtus likinis Hayat, sp. nov., O. seronis Hayat, sp. nov., Zaomma astera Hayat, sp. nov. The following 27 genera are newly recorded from Saudi Arabia: Achalcerinys Girault, Aphycus Mayr, Apoleptomastix Kerrich, Callipteroma Motschulsky, Cerchysiella Girault, Cerchysius Westwood, Charitopus Foerster, Cheiloneurus Westwood, Coelopencyrtus Timberlake, Copidosoma Ratzeburg, Helegonatopus Perkins, Homalotylus Mayr, Lamennaisia Girault, Leptomastidea Mercet, Leptomastix Foerster, Mahencyrtus Masi, Mayridia Mercet, Microterys Thomson, Neastymachus Girault, Ooencyrtus Ashmead, Paraclausenia Hayat, Prionomastix Mayr, Prochiloneurus Silvestri, Rhopus Foerster, Syrphophagus Ashmead, Tyndarichus Howard, Zaomma Ashmead. The following 27 species are newly recorded from Saudi Arabia: Achalcerinys lindus (Mercet), Anagyrus gracilis (Hayat), A. shahidi Hayat, Aphycus secundus (Mercet), Apoleptomastix bicoloricornis (Girault), Callipteroma sexguttata Motschulsky, C. testacea Motschulsky, Cerchysius ugandensis Kerrich, Charitopus andalusicus Mercet, Cheiloneurus elegans (Dalman), C. quadricolor (Girault), Coelopencyrtus krishnamurtii (Mahdihassan), Comperiella aspidiotiphaga Subba Rao, Copidosoma floridanum (Ashmead), Habrolepis obscura Compere & Annecke, Helegonatopus formosus (Mercet), Homalotylus flaminius (Dalman), Lamennaisia ambigua (Nees), L. nobilis (Nees), Leptomastix dactylopii Howard, L. tsukumiensis Tachikawa, Mayridia pulchra Mercet, Paraclausenia herbicola Hayat, Prochiloneurus aegyptiacus (Mercet), P. pulchellus Silvestri, Rhopus nigroclavatus (Ashmead), Syrphophagus aphidivorus (Mayr). Eleven species belonging to the genera Anagyrus Howard, Charitopus, Helegonatopus, Mayridia, Metaphycus Mercet, Ooencyrtus, Prionomastix, Syrphophagus, and Tyndarichus, were not identified to species for the reasons given in the text. The known species treated in this paper, except for some well known species, are illustrated with suitable figures, and some species are either diagnosed or redescribed.